2012
DOI: 10.1038/pr.2012.12
|View full text |Cite
|
Sign up to set email alerts
|

Height, BMI, and pituitary volume in individuals with and without isolated cleft lip and/or palate

Abstract: INTRODUCTION Individuals with isolated cleft lip and/or palate (ICLP) are often reported to be of shorter stature relative to peers, and the objective of this study was to explore the role of the pituitary in relationship to growth. METHODS Fifty-five males and 32 females with ICLP were compared to 121 healthy males and 158 healthy females with respect to height and BMI. Magnetic resonance imaging (MRI) scans were obtained from all ICLP participants and 47% of healthy group participants. RESULTS Males with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
0
13
1
1
Order By: Relevance
“…One such clinical study described olfaction deficits in adult males born with OFCs [37], while short stature has been well characterized and linked to possible pituitary dysfunction in affected patient populations [38][40]. While a recent study found no significant difference in pituitary volume between adult patients with OFCs and controls without clefts, pituitary structure and function were not specifically examined [41]. Consistent with increased volume of the forebrain septal region as described here, neuroimaging studies have identified shifts in tissue distribution in which the anterior cerebrum is enlarged [16], [42].…”
Section: Discussionmentioning
confidence: 99%
“…One such clinical study described olfaction deficits in adult males born with OFCs [37], while short stature has been well characterized and linked to possible pituitary dysfunction in affected patient populations [38][40]. While a recent study found no significant difference in pituitary volume between adult patients with OFCs and controls without clefts, pituitary structure and function were not specifically examined [41]. Consistent with increased volume of the forebrain septal region as described here, neuroimaging studies have identified shifts in tissue distribution in which the anterior cerebrum is enlarged [16], [42].…”
Section: Discussionmentioning
confidence: 99%
“…This relationship implies the existence of mechanical coordination in the growth of the pituitary gland alongside its enclosing skeletal compartment and may cause variations in the size of the gland, which are reflected in the shape and size of the sella turcica. Although some studies have demonstrated a relationship between cleft lip and palate [19][20][21] , Van der Plas et al [22] claimed that the pituitary is not involved in differences in isolated cleft lip and palate. In our study, there were differences between the cleft group and the control group in terms of the shape and size of the sella turcica, but it was only the length of the sella turcica that was higher in the cleft group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal insufficiency may develop during surgical procedures or infections, and middle ear infections are often seen (43). In patients with orofacial median clefts who also have limited adrenal reserve, such as ACTHcortisol deficiency and small-sized adrenal glands, reconstructive surgical operations of the orofacial median clefts may be life-threatening depending on the magnitude of the surgical procedure due to emerging hypoglycemia, hypotension, and cardiovascular collapse.…”
Section: Discussionmentioning
confidence: 99%